Concrete and masonry movements - Brooks, J. J. (Butterworth-Heinemann, 2015)
"Widely used in the construction of bridges, dams and pavements, concrete and masonry are two of the world’s most utilized construction materials. However, many engineers lack a proper understanding of the methods for predicting and mitigating their movements within a structure. Concrete and Masonry Movements provides practical methods for predicting and preventing movement in concrete and masonry, saving time and money in retrofitting and repair cost. With this book in hand, engineers will discover new prediction models for masonry such as: irreversible moisture expansion of clay bricks, elasticity, creep and shrinkage. In addition, the book provides up-to-date information on the codes of practice."--Provided by publisher.